Penerapan Manajemen Risiko Pembiayaan Pada Perusahaan Fintech Pegadaian Syari’ah - Wati, Pury Ganes; Wardana, Guntur Kusuma; Holis, Muhammad Nur (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Based on findings in the field, in its transactions Erahn.id provides online application services and is the first sharia fintech pawnshop in the city and district of Malang. Erahn.id can also provide free consultations regarding financial problems. Apart from having gone digital, or the application can be done online (website), the process of disbursing funds can also be done by transfer or cash. The entrustment service fee is charged on the estimated value of the pawned item, not on the value of the loan applied for. This is very different from other sharia pawnshops and is interesting to study. Erahn.id also prioritizes Islamic principles in implementing each of its business concepts. The aim of the research is to determine the implementation of financing risk management, the obstacles that occur in implementing financing risk management and resolving obstacles in implementing financing risk management in sharia pawnshop fintech companies. The method used is a qualitative method with a case study approach. This research was conducted at Erahn.id Jl. Simpang Wilis Indah, Gading Islamic Boarding School Block 1 No 13 Malang. The results show that the application of risk management at Erahn.id Malang was carried out with several risk management processes, namely: identification, measurement, monitoring, and risk control. Some obstacles also occur in the application of risk management at Erahn.id, such as forget to remind the customers who are passing the due date, the collateral item that is difficult to sell, and the lack of knowledge about authenticity and gold content. In resolving the obstacles faced when implementing financing risk management, the things that have been done by Erahn.id Malang are checking the database periodically, looking for the latest market price information for the collateral items, and upgrading knowledge from relations owned by the founder of Erahn.id Malang. This research can introduce and enhance people's insight about pawnshop with sharia principles. Pawn shops with sharia principles have developed into digital go-based companies that can efficiently compete with other finteches.